Difference in explosive power and agility between faster and slower football players aged 15-18 - Majkic, B.; Aleksic, A. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
During the football match high-intensity activities occur approximately every 90 seconds, and the distance covered during the sprint (1.5 m up to 105 m) indicates that player is required both to accelerate and to develop a maximum speed. To the best of authors` knowledge, no study aimed to examine the explosive power (EP) and agility of football players when divided into groups of faster and slower players. In this regard the aim of this study was to determine the differences in explosive power and agility in faster and slower football players aged 15-18. The study involved 50 youth football players (16.4±0.9 yrs, 177.8±5.1 cm, 72.4±4.7 kg) competing in a top youth league. At the time of testing all respondents had training experience of 9±1.3 years and they were divided into two groups: faster players (n=25) and slower players (n=25). EP was determined by CMJ, CMJ free arm and SJ tests using Opto-jump (Microgate, Italy). Agility was assessed by T-test, Slalom, 4x5 m and 9-3-6-3-9, as well as running speed at 10 and 30 m using Witty photocell gates (Microgate, Italy). Significant difference on 10 m acceleration test have been observed in CMJ, SJ and T-test (p=.043, p=.041 and p=.022, respectively) and on a 30 m run test in CMJ, SJ, T-test, 4x5 m and 9-3-6-3-9 tests (p=.000, p=.002, p=.022, p=.000, and p=.019, respectively). Also percentage difference is biggest in EP tests (SJ=11.18%; CMJ=11.96%; CMJ free arm=8.86%). Statistically, the difference is much more visible when the classification of players is done on the basis of 30 m running than when it is done based on 10 m acceleration. It can be concluded that there is a difference between faster and slower players in all of the tested parameters when the maximum speed is taken as a criterion. When it comes to acceleration of 10 m there is a statistical difference between faster and slower players in certain segments of EP, while the difference in agility parameters is questionable because only T-test showed a statistically significant difference. The main limitations of this study are sub-elite subjects and big difference between youngest and oldest player. Therefore, future studies should consider these limitations and divide players by playing positions.